2020
DOI: 10.1038/s41477-020-0654-y
|View full text |Cite
|
Sign up to set email alerts
|

Global synthesis of effects of plant species diversity on trophic groups and interactions

Abstract: Numerous studies have demonstrated that plant species diversity enhances ecosystem functioning in terrestrial ecosystems, including diversity effects on insect arthropods (herbivores, predators and parasitoids) and plants. Yet, the effects of increased plant diversity across trophic levels in different ecosystems and biomes have not yet been explored on a global scale. Through a global meta-analysis of 2914 observations from 351 studies, we found that increased plant species richness reduced herbivore abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 55 publications
4
88
1
1
Order By: Relevance
“…However, plant diversity likely constrains herbivore performance by means other than just the dilution of nutrient concentrations, as predation rates have also been shown to increase at high levels of plant diversity (18,19). This process is described by the "enemies hypothesis" (16), which proposes that higher plant species diversity will provide greater refuge for predators [e.g., (20)], leading to greater suppression of herbivores via top-down control (19). Given that both bottom-up and top-down forces operate simultaneously, increasing plant diversity likely reduces herbivore impacts on plants through these simultaneous multitrophic controls in food webs.…”
Section: Introductionmentioning
confidence: 99%
“…However, plant diversity likely constrains herbivore performance by means other than just the dilution of nutrient concentrations, as predation rates have also been shown to increase at high levels of plant diversity (18,19). This process is described by the "enemies hypothesis" (16), which proposes that higher plant species diversity will provide greater refuge for predators [e.g., (20)], leading to greater suppression of herbivores via top-down control (19). Given that both bottom-up and top-down forces operate simultaneously, increasing plant diversity likely reduces herbivore impacts on plants through these simultaneous multitrophic controls in food webs.…”
Section: Introductionmentioning
confidence: 99%
“…For specialist enemies, he predicted that populations would fluctuate less "because the refuge provided by a complex environment enables host species to escape widespread annihilation" [20]. The intuitive predictions of the "enemies" hypothesis are often supported in agricultural ecosystems (e.g., [21,23,24]). However, it might be that in communities with long-lived plant individuals, such as forests, plant diversity-facilitated top-down control might differ from annual communities where consumer assemblages need to reassemble anew each year.…”
Section: Introductionmentioning
confidence: 99%
“…Recently discovery revealed that altering the cropping pattern from intensive monoculture to diversified agriculture, could help to withstand the climate change, protect vital wildlife and alleviate the long-term loss of biodiversity outside natural protected area in the future [51]. Besides, increasing plant species diversity could promote beneficial trophic interactions between insects and plants, ultimately contributing to increased ecosystem services [52] Thus, we suggested that more wild edible plants could be introduced and cultivated in the nearby protected areas, farming land, rubber forest, tea plantation field and village owned forest, homegardens as well as any suitable sites to build corridors or ex situ reserve areas for some important, rare, medicinal and edible plants, conserve more plant genetic resources and establish a diversified agriculture. Moreover, modern plantation technology should also be updated, and the cultivation and domestication of some preferred wild edible plants should be strengthened by cooperating with some food industries to reduce field collection, increase economic income and contribute to the sustainable development of local communities.…”
Section: Important Role Of Traditional Knowledge To Local Communitiesmentioning
confidence: 99%